Monte Carlo modelling of single and multiple Compton scattering profiles in a concrete material - Tarim, Ua; Ozmutlu, En; Gurler, O.; Yalcin, S.; Gundogdu, O.; Sharaf, Jm; Bradley, Da (Elsevier BV, 2013)
Abstract A Monte Carlo simulation study has been conducted of 60Co photons Compton scattered in concrete, illustrating the degraded energy spectra of gamma-ray radiation. Results are produced representing a NaI(Tl) detector model. We were able to analyse energy distributions of photons that reach the detector system after suffering several successive Compton scatterings in the target. The predicted decrease in intensity of single- and multiple-scattering peaks with increase in thickness of the target medium are in good agreement with experimental observations and findings reported by others.